The Effectiveness of The Implementation of Legal Protection for Vocational High School Students Who Have Had Work Accidents in The Field Work Practice: A Case Study at The Alantara Sanur - Ni Wayan Eka Damayanti; Ni Nyoman Putri Purnama Santhi; I Putu Harry Suandana Putra; Ni Putu Yuliana Kemalasari (West Science Law and Human Rights, 2026)
Field Work Practice (Praktik Kerja Lapangan/PKL) is an essential component of the Vocational High School (SMK) curriculum intended to equip students with genuine workplace experience, yet its implementation within the hospitality industry carries a real risk of occupational accidents that may harm students who hold the dual status of learners and apprentices. This study aims to identify and analyze the effectiveness of legal protection for SMK students who experienced occupational accidents during PKL at The Alantara Sanur, and to identify the supporting and inhibiting factors affecting that effectiveness. The study employs an empirical juridical method with a descriptive character, using the fact approach, statute approach, and conceptual approach. Data were collected through document study, interviews, and field observation. The findings indicate that the implementation of legal protection for PKL students at The Alantara Sanur has not been fully effective. Based on Soerjono Soekanto's five factors of legal effectiveness, a gap between das sollen and das sein was found across all dimensions, including normative gaps in regulation (Law No. 1 of 1970, Law No. 13 of 2003, and Ministerial Regulation No. 50 of 2020) that fail to explicitly provide social security for PKL students, weak supervision by schools and industry, unstructured occupational safety training, low legal awareness among students and hotel staff, and a speed-oriented work culture. The inhibiting factors are multilevel and mutually reinforcing, while the supporting factors an existing normative framework, an improvable SOP and MoU, and industry good faith may serve as a foundation for reform. This study recommends regulatory refinement accompanied by a tripartite supervisory mechanism among schools, industry, and government, as well as the strengthening of structured occupational safety training for PKL students.